UJI AKTIVITAS ANTI DIARE SIRUP LIOFILISAT EKSTRAK BUAH HARENDONG (Melastoma affine D. Don) TERHADAP MENCIT (Mus musculus L.) - Imas Maesaroh; Marini Marini (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
Harendong fruit (Melastoma affine D. Don) is empirically used by the community in the Mount Ciremai National Park as an anti-diarrheal medicine. Based on the results of research conducted by Safitri, et al, it is known that the extract of raw harendong fruit contains flavonoid and phenolic compound. Phenolic compound that is commonly found in fruit is tannin. Additionally, based on the literature, tannin has been proven to be useful as anti-diarrheal while flavonoid is useful as anti-bacterial. This study aims at determining the activity of harendong fruit extract syrup as anti-diarrheal in mice (Mus musculus L.). The research method in this study is carried out by giving oleum ricini as an anti-diarrheal inducer compared to positive control (loperamid HCl 11 mg / kg bw suspension) and negative control (Na CMC suspension). The harendong fruit lyophilisate syrup is made with different concentrations, namely 0.5%, 1% and 1.5%. Evaluation of the anti-diarrheal effect includes consistency of slimy / watery stools, soft and normal stools (including water absorption diameter, time of occurrence of diarrhea and stool weight), frequency of diarrhea and duration of diarrhea. The results of the test for the antidiarrheal effect of harendong fruit lyophilisate syrup at a dose of 0.5% has a weaker effect in suppressing the occurrence of diarrhea than the positive control. Then, harendong fruit lyophilisate syrup at a dose of 1% shows almost the same antidiarrheal effect compared to the positive control, while harendong fruit lyophilisate syrup with a dose of 1.5% has a stronger effect in suppressing the occurrence of diarrhea than the positive control.